Spousal Violence in Bangladesh: A Call for a Public-health Response - Johnston, Heidi Bart; Naved, Ruchira Tabassum (Journal of Health, Population and Nutrition, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Spousal violence against women is a serious public-health issue. Although there is a growing body of literature on this subject, there are still many unanswered questions regarding the prevalence of this violence, the risk factors, the consequences, and how to address the issue. The purpose of this literature review is to organize and synthesize the empirical evidence on spousal violence against women in Bangladesh and to provide direction for both researchers and practitioners for future work in this area. The review suggests that spousal violence against women is high in Bangladesh. The list of correlates is long and inconclusive. Although there is evidence on adverse consequences of this violence on health of women and their children, more research is needed to explore the multifaceted consequences of violence for women, children, families, and communities. Action research is needed to develop and test preventive and curative interventions. Key words: Gender; Review literature; Violence; Violence, Spousal; Bangladesh doi:10.3329/jhpn.v26i3.1903 J Health Popul Nutr 2008 Sept:26(3):366-377